eGovernance: Information and Communication Technology, Knowledge Management and Learning Organisation Culture - Berce, J.; Lanfranco, S.; Vehovar, V. (Informatica)
eGovernance: Information and Communication Technology, Knowledge Management and Learning Organisation Culture